Genetic diversity of alpine Dryas octopetala populations at their southern distribution limit in Europe. (13th April 2021) - Varsamis, Georgios; Merou, Theodora; Karapatzak, Eleftherios; Papageorgiou, Aristotelis C.; Fotiadis, Georgios; Tsiftsis, Spyros
Abstract : The arctic–alpine species Dryas octopetala has its southernmost European distribution in the northern part of Greece, where it forms isolated populations in three mountainous regions: Falakron, Tzena and Orvilos. This study aimed at estimating the intrapopulation genetic diversity and the overall genetic structure of these populations. A total of 20 randomly amplified polymorphic DNA (RAPD) markers were used. RAPD marker profiles revealed population differentiation, with Orvilos being the most differentiated population, indicating either genetic divergence or an independent origin. Intrapopulation genetic diversity indices were relatively low in all populations. Although isolation seem to have affected the genetic structure of D. octopetala populations at their southernmost European distribution limit, clonality and longevity of individuals might have contributed to maintaining their genetic diversity. The results emphasize the need for designing ex situ conservation management plans for conserving isolated alpine D. octopetala populations in the face of climate change.